An Analysis of Language Anxiety on Students’ Academic Speaking Performance - Vina Asterina; Muhammad Tahir; Fitriyani Fitriyani (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
Language anxiety remains one of the most critical affective factors influencing students’ success in English as a Foreign Language (EFL) learning, particularly in speaking performance. This study investigates the types of language anxiety and their impacts on students’ academic speaking performance at Universitas Balikpapan. The research aims to (1) identify the dominant types of language anxiety experienced by students and (2) examine how anxiety affects fluency, accuracy, and complexity in academic speaking. A descriptive qualitative method was employed with data gathered from twenty second-semester students of the English Literature program. Instruments included the Foreign Language Classroom Anxiety Scale (FLCAS), observation checklists, and recorded oral performances. Results revealed that trait anxiety was the most prevalent, experienced by 45% of participants, followed by situation-specific anxiety (30%) and state anxiety (25%). Regarding impact, language anxiety significantly reduced students’ fluency, with most classified as disfluent or very disfluent speakers. However, accuracy and complexity were less affected; most students achieved good or excellent ratings. These findings suggest that while anxiety predominantly impairs the spontaneity of speech, it does not heavily disrupt students’ ability to produce correct or comprehensible language. This study highlights the need for targeted classroom interventions to address anxiety-related fluency issues while reinforcing existing strengths in accuracy and complexity.